1996
DOI: 10.1007/s001250050560
|View full text |Cite
|
Sign up to set email alerts
|

Examination of two genetic polymorphisms within the renin-angiotensin system: no evidence for an association with nephropathy in IDDM

Abstract: Premature cardiovascular disease is common in insulin-dependent diabetic (IDDM) patients who develop diabetic nephropathy. Genetic polymorphism within the renin-angiotensin system has been implicated in the aetiology of a number of cardiovascular disorders; these loci are therefore candidate genes for susceptibility to diabetic renal disease. We have examined the angiotensin converting enzyme insertion/deletion polymorphism and angiotensinogen methionine 235 threonine polymorphism in a large cohort of Caucasia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…These findings are in keeping with earlier work in which the frequency of the I allele was significantly lower in those with albuminuria, suggesting that possession of the I allele may be protective[52]. There have, however, been several studies in which no association was found between ACE genotype and nephropathy[53–56].…”
Section: Ace Polymorphism and Microvascular Diseasesupporting
confidence: 90%
“…These findings are in keeping with earlier work in which the frequency of the I allele was significantly lower in those with albuminuria, suggesting that possession of the I allele may be protective[52]. There have, however, been several studies in which no association was found between ACE genotype and nephropathy[53–56].…”
Section: Ace Polymorphism and Microvascular Diseasesupporting
confidence: 90%
“…Results of the distribution of the ACE genotypes in previous studies on adult populations are conflicting [7,16,21,30–32]. Some studies described a higher prevalence of the DD genotype in younger than in older people [2,33] and others found this genotype to be associated with human longevity [34].…”
Section: Discussionmentioning
confidence: 99%
“…This polymorphism has also been examined in diabetic nephropathy, again with conflicting results. In our own much larger study [49], and others [57], no such association was found, although one study has suggested an association of the TT genotype with elevated blood pressure in patients with nephropathy [58]. In our own much larger study [49], and others [57], no such association was found, although one study has suggested an association of the TT genotype with elevated blood pressure in patients with nephropathy [58].…”
Section: Angiotensinogen Genementioning
confidence: 59%
“…Thus the II genotype is associated with low levels of serum ACE, whereas the DD genotype is associated with high levels, with ID genotypes having intermediate levels of ACE. However, our own and other subsequent large studies examining over 1000 patients with and without nephropathy have shown no association between nephropathy and the D allele [47][48][49]. In diabetic nephropathy two small studies have suggested an association between the D allele of the ACE gene and nephropathy [45,46].…”
Section: Angiotensin I-converting Enzyme Genementioning
confidence: 72%